Modern Approach of International Cooperation in Higher Education - Kamilova Nargiza Abdukahorovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article reveals the issues of internationalization of the higher education system, improving its quality, and the introduction of international training standards. At the same time, the process of internationalization of higher education, along with advantages, carries some problematic nuances, the solution of which requires a competent approach through the prism of international cooperation.